Distribution of blood groups among blood donors at a tertiary care hospital in Southern Rajasthan - Dr. Suraj Jain; Dr. Preeti Agrawal; Dr. Shashi Sujanani (Tropical Journal of Pathology and Microbiology, 2018)
Introduction: Blood grouping is one of the essential aspects of blood transfusion practice. ABO and Rhesus (Rh) blood groups are the two most important blood group systems among the various types identified so far. Distribution of ABO blood group varies indifferent geographical and ethnic groups.Objectives: This study was carried out to determine the distribution pattern of blood groups among blood donors at a tertiary care hospital of Southern Rajasthan. Methods: It is a retrospective study covering a period of 3 years from July 2014 to June 2017 that includes 3718 blood donors of which 1297are voluntary and 2421are replacement blood donors. Data on the ABO and Rh blood group type of all blood donors was collected and analysed.Result: The most common ABO blood group type was Group B (36.6%) followed by group O (32.1%), group A (22.8%) and group AB (8.5%) respectively. The distribution of Rh(D) blood group type revealed 93.5% as Rh-positive and 6.5% as Rh-negative.Conclusion: The most common ABO blood group type in our region (Southern Rajasthan) is Group B followed by O and A while, AB is the least common type. Knowledge of the blood group distribution pattern is essential for the effective delivery of blood banking services.